Survival/coping strategies of women in Internally Displaced People’s (IDPs) camps : a study In New Kuchingoro camp, Federal Capital Territory (FCT), Abuja, Nigeria - Pikirayi, Innocent (University of Pretoria, 2022)
Thesis (PhD (Development Studies))--University of Pretoria, 2022.